Mahasiswa dan serba-serbi problematikanya dalam mengikuti perkuliahan deutsch III secara daring - Ramadhani, Shabrina; Retnantiti, Sawitri (Fakultas Sastra Universitas Negeri Malang, 2022)
The Covid-19 pandemic at the beginning of 2020 caused many changes, including in the world of education, such as the implementation of the distance learning method (PJJ) to reduce the spread of the Covid-19 virus. In practice, distance learning (PJJ) which is carried out using an online system or in a network (online) cannot be separated from the problems that occur. This research was conducted using a quantitative descriptive approach and aims to describe the factors that constrain students of the German Language Education Study Program at the State University of Malang in participating in the online Deutsch III lecture process. The result is that there are internal and external factors in the problems of online learning. The problem with internal factors is related to student motivation in participating in online learning. The motivation of students is very low, causing other internal problems, namely the low ability of students to understand the material. Then the problem of external factors is regarding the learning process and supporting facilities during online learning. Students often experience network problems, and an unfavorable environment that causes students to lack concentration during the online learning process.